2020
DOI: 10.1136/openhrt-2020-001258
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities in advanced heart failure: James Lind alliance priority setting partnership

Abstract: ObjectiveTo determine research priorities in advanced heart failure (HF) for patients, carers and healthcare professionals.MethodsPriority setting partnership using the systematic James Lind Alliance method for ranking and setting research priorities. An initial open survey of patients, carers and healthcare professionals identified respondents’ questions, which were categorised to produce a list of summary research questions; questions already answered in existing literature were removed. In a second survey o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The final top ten research priorities were decided in agreement between consumers and nurses resulting in a combined agreed priority list, an achievement that has not always been possible when targeting both groups at the same time (Taylor et al, 2020;Tume et al, 2020). 'Access to service' was the highest ranked theme.…”
Section: Discussionmentioning
confidence: 99%
“…The final top ten research priorities were decided in agreement between consumers and nurses resulting in a combined agreed priority list, an achievement that has not always been possible when targeting both groups at the same time (Taylor et al, 2020;Tume et al, 2020). 'Access to service' was the highest ranked theme.…”
Section: Discussionmentioning
confidence: 99%
“…For many patients with HF, the quality of daily living may be more important than the length of life 31 . In a recent James Lind Alliance Priority Setting Partnership, the number one research priority set by patients, carers, and clinicians was ‘identification of treatments that have the biggest impact on QoL of people with advanced heart failure’ 32 …”
Section: Discussionmentioning
confidence: 99%
“…31 In a recent James Lind Alliance Priority Setting Partnership, the number one research priority set by patients, carers, and clinicians was 'identification of treatments that have the biggest impact on QoL of people with advanced heart failure'. 32 In more recent studies, improvements in KCCQ clinical and total summary scores have been reported, alongside clinical outcomes, including the large HFrEF trials of sacubitril/ valsartan, 33 dapagliflozin, 27 and empagliflozin. 26 Within-study comparisons of generic and disease-specific HRQoL tools are also being undertaken.…”
Section: Policy and Practicementioning
confidence: 99%
“…The priorities and expectations of patients and clinicians often differ. Clinicians frequently are more concerned with cardiac anatomy and physiology, reducing mortality, and specific management issues, while patients just wish to feel better 28,35 . However, both clinicians and patients generally assign high priority to improving HRQoL.…”
Section: Using Patient‐reported Outcomes To Improve Patient Carementioning
confidence: 99%